Sexual and reproductive health aspects in women with polycystic ovary syndrome: An integrative review - Mehri Kalhor; Eesa Mohammadi; Shadab Shahali; Leila Amini; Lida Moghaddam-Banaem (International Journal of Reproductive BioMedicine, 2022)
Abstract Background: Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders in women worldwide, affecting their sexual and reproductive health (SRH). Objective: This integrative review aimed to identify SRH aspects in women with PCOS by consolidating the findings from previous studies. Materials and Methods: The present integrative review was conducted through an electronic systematic review search of 1052 manuscripts published from April 2000 to March 2020 using PubMed, SCOPUS, Web of Science, Embase, Google Scholar, MEDLINE, Science Direct, Ovid, and the Cochrane Library. After at least 2 researchers evaluated the articles based on the inclusion and exclusion criteria, 27 papers were accepted. The data were analyzed by thematic analysis. Results: 9 main themes of SRH were obtained: 1) the impact of PCOS-related complications on reproductive health; 2) the lifelong effect of PCOS on reproductive patterns; 3) PCOS and adverse reproductive and pregnancy outcomes; 4) women's need for understanding complications; 5) the financial burden of the disease; 6) women's life experiences and quality of life; 7) sexual disorders; 8) psychological concerns and issues; and 9) femininity feelings and roles. Conclusion: We were able to identify and categorize various aspects of SRH needs for women with PCOS. These categories can facilitate a more comprehensive assessment of SRH, including previously neglected areas. We suggest that these aspects should be considered in the health plans of women with PCOS.